Expanding Coverage of Good Quality Private Pensions - Price, William; Rawlins, Marlon; Stewart, Fiona (World Bank, Washington, DC, 2016)
The FIRST Lessons Learned Series is a collection of FIRST's technical and functional insights gained from FIRST funded engagements. This knowledge note shares useful lessons from FIRST-funded pension projects led by the Finance and Markets Global Practice at the World Bank Group, which supported many countries in their efforts to improve the coverage of good-quality pensions and in increasing the supply of pension assets that can safely and sustainably fund long-term investment.